2017
DOI: 10.1253/circj.cj-16-0748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vessel Diameter Measured by Preprocedural Computed Tomography Angiography on Immediate and Late Outcomes of Endovascular Therapy for Iliac Artery Diseases

Abstract: incidence of procedural failure and periprocedural complications has been reported to be 1-5% and 4-20%, respectively, frequencies that are still clinically significant. 5- 12 We therefore investigated whether vessel diameters measured by preprocedural CTA affects the immediate (procedural failure or vessel-specific complications) and late outcomes (the need of target lesion revascularization [TLR]) of endovascular therapy for iliac artery disease. Methods SubjectsBetween 2005 and 2013, a total of 590 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A study by Hong et al28 found during endovascular treatment for common and external iliac artery disease, smaller target lesion artery diameters, as determined via CTA, were independent predictors of procedural failure. Similar findings were demonstrated in patients with peripheral artery disease undergoing lower extremity bypass whereby great saphenous graft conduit diameter <3.5 mm was a primary technical determinant of graft failure 29.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hong et al28 found during endovascular treatment for common and external iliac artery disease, smaller target lesion artery diameters, as determined via CTA, were independent predictors of procedural failure. Similar findings were demonstrated in patients with peripheral artery disease undergoing lower extremity bypass whereby great saphenous graft conduit diameter <3.5 mm was a primary technical determinant of graft failure 29.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between arterial diameter and procedural success or failure has been previously studied in extracranial vascular disease. Hong et al [23] reported that smaller diameters of the external iliac artery and the target lesion artery were independent predictors of procedural failure or vessel-specific complications in endovascular treatment of iliac artery disease. It is possible that a smaller vessel diameter is also related to procedural failure during intracranial endovascular therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between vessel diameter and procedural outcomes was reported in a study of 254 patients undergoing endovascular treatment for iliac ar-tery diseases. The investigators showed that the target vessel diameter measured using CT angiography was an independent predictor of procedural failure or vessel-specific complications [31].…”
Section: Possible Reasons For More Failure Of Recanalization In Womenmentioning
confidence: 99%